2009
DOI: 10.1063/1.3151995
|View full text |Cite
|
Sign up to set email alerts
|

Radial thermal expansion of pure and Xe-saturated bundles of single-walled carbon nanotubes at low temperatures

Abstract: The radial thermal expansion coefficient α r of pure and Xe-saturated bundles of singlewalled carbon nanotubes has been measured in the interval 2.2-120 K. The coefficient is positive above T = 5.5 K and negative at lower temperatures. The experiment was made using a low temperature capacitance dilatometer with a sensitivity of 2·10 -9 cm and the sample was prepared by compacting a CNT powder such that the pressure applied oriented the nanotube axes perpendicular to the axis of the cylindrical sample. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 52 publications
(79 reference statements)
2
58
0
Order By: Relevance
“…It is found in [2] that the air-oxidative treatment applied to open the CNT ends enhanced the Xe sorption. However, our comparative experiments on saturating o-SWNT and c-SWNT bundles with H 2 [4] showed that the c-SWNTs absorbed more hydrogen than the oxidated ones.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found in [2] that the air-oxidative treatment applied to open the CNT ends enhanced the Xe sorption. However, our comparative experiments on saturating o-SWNT and c-SWNT bundles with H 2 [4] showed that the c-SWNTs absorbed more hydrogen than the oxidated ones.…”
Section: Resultsmentioning
confidence: 99%
“…Its design and the experimental technique are detailed elsewhere [2]. According to the manufacturer, the starting CNT powder (CCVD method, Cheap Tubes, USA) contained over 90% of SWNTs, the average outer diameter of the tubes being 1.1 nm.…”
Section: Experimental Techniquementioning
confidence: 99%
See 3 more Smart Citations